Risk factors of stroke-related sarcopenia: a systematic review and meta-analysis - Yan, Huan; Li, Juan; Xian, Lihong; Li, Yujie; Li, Simin; Wen, Qinghua (Frontiers in Aging, 2025)
BackgroundThe presence of sarcopenia at the time of stroke may deteriorate the rehabilitation and functional outcomes. There is no consensus on the factors associated with stroke-related sarcopenia because previous studies produced inconsistent and disputed results. Therefore, we screened the possible risk factors by meta-analysis.MethodsStudies published before March 2024 on risk factors with stroke-related sarcopenia were searched through PubMed, Embase, Web of Science, CINAHL, Cochrane Library, CNKI, Wan Fang, CBM, and VIP library databases. Two researchers independently screened the articles to extract the information and to evaluate their quality. Meta-analysis was then performed using Revman 5.4 software to determine the significant risk factors for patients with stroke-related sarcopenia.ResultsA total of 14 studies (n = 3,113) were selected to determine the following factors that were statistically significant in patients with stroke-related sarcopenia: Age (OR = 1.04; 95% CI: 1.02, 1.06; P < 0.0001), tube feeding (OR = 3.98; 95% CI: 2.12, 7.47; P < 0.0001), pre-stroke sarcopenia (OR = 1.84; 95% CI: 1.39, 2.43; P < 0.0001), atrial fibrillation (OR = 1.53; 95% CI: 1.15, 2.02; P = 0.003), NIHSS score (OR = 1.48; 95% CI: 1.21, 1.81; P = 0.0001), and osteoporosis (OR = 1.801; 95% CI: 58, 2.04; P < 0.00001). BMI (P = 0.71), FOIS (P = 0.80), time since stroke (P = 0.34), and calf circumference reduction (P = 0.48) were not identified as risk or protective factors after stroke (P < 0.05).ConclusionOur results identified various risk factors for stroke-related sarcopenia which should be considered and studied by healthcare organizations and professionals to improve the health of stroke patients.Systematic Review RegistrationPROSPERO, Identifier CRD42024545757.